1995
DOI: 10.1590/s0006-87051995000200002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grape genotype, ripening season, seed trace size, and culture date on in ovule embryo development and plant formation

Abstract: Eighteen seedless grape genotypes differing in ripening season (early, mid and late) and in seed trace size (small, medium and large) were harvested at 6, 10, 14, 18 and 22 weeks past bloom (wpb). Using embryo rescue techniques it was studied if embryo do abort as the fruit matures and what percent embryos remain viable at later stages. The size of seed trace was also investigated to determine its influence on embryo viability during maturation. It was found that genotype have great influence on embryo culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
(14 reference statements)
0
23
0
1
Order By: Relevance
“…The grape hybrids used in this study were derived from the "Thompson Seedless" and "Superior Seedless" Brazilian clones crossing, obtained from cultivated plants in an experimental field of Embrapa Tropical Semiarid, according to the procedures proposed by [7]. Eight weeks after the crossing, 152 ovules were collected from the obtained fruits, and inoculated into the culture media proposed by [8] under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The grape hybrids used in this study were derived from the "Thompson Seedless" and "Superior Seedless" Brazilian clones crossing, obtained from cultivated plants in an experimental field of Embrapa Tropical Semiarid, according to the procedures proposed by [7]. Eight weeks after the crossing, 152 ovules were collected from the obtained fruits, and inoculated into the culture media proposed by [8] under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…This efficiency can be altered as a result of time out after anthesis (García et al, 2000); growth regulators Nookaraju et al, 2007); grape variety used (Hewstone et al, 2006); intensity and type of pruning (Dalal et al, 1992;Ponce et al, 2009); genotype, harvest time and embryo size (Ramming and Emershad, 1990;Pommer et al, 1995) thus culture medium and time of in vitro culture (Valdez, 2005). Based on the above, the present study aims to evaluate the efficiency of embryo rescue technique in f1 individuals from hybridizations performed through classical genetic techniques using different varieties of seedless grapes.…”
Section: Materials Vegetalmentioning
confidence: 99%
“…Esta eficiencia puede alterarse como resultado del tiempo de espera después de antesis (García et al, 2000); reguladores de crecimiento Nookaraju et al, 2007); variedad de uva utilizada (Hewstone et al, 2006); intensidad y tipo de poda (Dalal et al, 1992;Ponce et al, 2009); genotipo, época de cosecha y tamaño del embrión (Ramming y Emershad, 1990;Pommer et al, 1995) así como el medio de cultivo utilizado y tiempo de cultivo in vitro (Valdez, 2005). Con base en lo anterior mencionado, el presente trabajo tiene como objetivo evaluar la eficiencia de la técnica de rescate de embriones en individuos f1 provenientes de hibridaciones realizadas mediante técnicas de genética tradicional utilizando diferentes variedades de uva sin semilla.…”
Section: Introductionunclassified
“…Results indicated that in ovulo embryo rescue can be improved by increasing CaCl2 concentration and incorporating casein hydrolysate supplement in the basal medium, by exploiting genotypic differences using seedless parents yielding higher proportions of rescued hybrids and, possibly, by understanding environmental effects on female parents to maximize the number of hybrids produced. Pommer et al ( 1995 ) used 18 seedless grape genotypes differing in ripening season (early, mid and late) and in seed trace size (small, medium and large) and harvested at 6, 10, 14, 18 and 22 weeks post-bloom (wpb). Using embryo rescue techniques, it was studied if embryos aborted as the fruit matured and what percentage of embryos remained viable at later stages.…”
Section: Seedless Grapesmentioning
confidence: 99%